2021
DOI: 10.3389/fgene.2021.730495
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Analysis of Complete Chloroplast Genomes of 13 Species in Epilobium, Circaea, and Chamaenerion and Insights Into Phylogenetic Relationships of Onagraceae

Abstract: The evening primrose family, Onagraceae, is a well defined family of the order Myrtales, comprising 22 genera widely distributed from boreal to tropical areas. In this study, we report and characterize the complete chloroplast genome sequences of 13 species in Circaea, Chamaenerion, and Epilobium using a next-generation sequencing method. We also retrieved chloroplast sequences from two other Onagraceae genera to characterize the chloroplast genome of the family. The complete chloroplast genomes of Onagraceae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 95 publications
(80 reference statements)
1
7
0
Order By: Relevance
“…ranged from 159,496 bp to 160,416 bp, and Epilobium sp. ranged from 160,748 bp to 161,144 bp [78]. Our study revealed that the size of the complete chloroplast of Ludwigia (Onagraceae subfamily Ludwigioideae) ranged from 159,369 bp to 159,584 bp, which is remarkably similar to other Onagraceae plants (average length of 162,030 bp).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…ranged from 159,496 bp to 160,416 bp, and Epilobium sp. ranged from 160,748 bp to 161,144 bp [78]. Our study revealed that the size of the complete chloroplast of Ludwigia (Onagraceae subfamily Ludwigioideae) ranged from 159,369 bp to 159,584 bp, which is remarkably similar to other Onagraceae plants (average length of 162,030 bp).…”
Section: Discussionsupporting
confidence: 64%
“…and Epilobium sp. (38.1 to 38.2%, [77]) and more generally for the order Myrtales (36.9-38.9%, with the average GC content being 37%, [78]).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The cp has its genetic material separate from the nucleus and its genome, generally 120 to 170 kb in size, and encodes for 120 to 130 genes 13 . The cp genome usually has a quadripartite structure with a large single copy, a small single copy, and two inverted repeat (IRa and IRb) regions 14 . Homologous recombination occurs between these two inverted regions 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the in uence of replication mechanisms on base bias differs in the AT and CG asymmetries. Replication is generally strong for GC skew, whereas AT skew is caused by coding sequence-related mechanisms [42,43].…”
Section: Codon Usage Bias In the Cp Genome Of C Nannophyllamentioning
confidence: 99%